Contextualization of Hadith about Tolerance for Religious and Cultural Diversity - Alkadri Alkadri; Zarul Arifin; Harles Anwar (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to understand the contextualization of hadith regarding tolerance to religious and cultural diversity with a focus on the meaning of the text, the historical context of tolerance at the time of the Prophet and the contextualization of hadiths . Data analysis was in the form of content analysis. It was found that first, there were six editorials of hadith tolerance using the word samaha which means compassion, generosity and is equated with the word patient. Second, the historical context of the prophet's tolerance attitude was recorded in building a pluralist society in the form of forgiveness, good prejudice, recognizing other religions and cooperate with each other. Third, the contextualization of the hadith that the basic concept of Islam in a pluralist society must be based on the principles of living in harmony, peace and prioritizing spirituality and humanity and ignoring group subjectivity. Departing from this finding, the universality of Islamic teachings is able to respond to the social reality of Indonesian society through religious tolerance in cultural and religious diversity